Dural Closure Method Using Dural Suture and Polyglycolic Acid Nonwoven Fabric in the Endoscopic Endonasal Approach - Tanioka, Daisuke; Natori, Ikuya; Kobayashi, Yusuke; Shimizu, Katsuyoshi; Mizutani, Tohru (Journal of Neurological Surgery Part B: Skull Base, 2024)
Introduction The indications for surgery using the endoscopic endonasal approach (EEA) for tumors in the sella turcica and parasellar region are expanding. However, the risk of cerebrospinal fluid (CSF) leakage is also increasing. Therefore, to prevent postoperative CSF leakage, it is essential to use safe reconstruction methods for the sella turcica. A polyglycolic acid (PGA) nonwoven fabric is applied during dural reconstruction in neurosurgery. Nevertheless, its suitability for sella turcica reconstruction has not been validated.Methods This study enrolled patients who underwent lesion resection using EEA, followed by sella turcica reconstruction using the dural closure method and the simple and robust suture and PGA (S-PGA) method. The outcomes of the surgery were compared with those of fat-based reconstructive procedures performed prior to the introduction of the S-PGA method.Results In total, 325 patients underwent dural closure using the S-PGA method. The incidence rates of postoperative CSF leakage were 0.8% for the S-PGA method and 5.2% for the fat-filling method. This finding indicated significant improvement in the incidence rates of postoperative CSF leakage (P < 0.01). The S-PGA method did not affect radiogram interpretation of magnetic resonance imaging performed at 3 months after surgery due to the absence of intrasellar fat filling.Conclusion The S-PGA method in EEA is a simple and reliable technique for decreasing the risk of postoperative CSF leakage to the greatest extent possible. Hence, it can be an excellent option for skull base reconstruction.
Keywords: polyglycolic acid nonwoven fabric; dural suture; endoscopic endonasal approach; cerebrospinal fluid leakage; reconstruction of skull base